PENGARUH PENGGUNAAN MEDIA KOMIK MATEMATIKA DENGAN BANTUAN POWERPOINT TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA DI SMK ISTIQLAL DELITUA PENGARUH PENGGUNAAN MEDIA KOMIK MATEMATIKA DENGAN BANTUAN POWERPOINT TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA SISWA DI SMK ISTIQLAL DELITUA - Putri Amanda Siregar; Rosliana Siregar (Universitas Islam Sumatera Utara, 2017)
This research aims to determine the effect of using comics media mathematics with the help of powerpoint on motivation and results of students’ mathematics learning on the subject of the matrix inverse order 2x2. This research was conducted in SMK Istiqlal Delitua. The population in this research are 486 students of class X. The sampling in this research using purposive sampling technique are 35 students of class X.AP-1. Based on the results of the test data requirements known that motivation data as well as results of the students’ mathematic learning are distributed normally. Motivation data an average score is 99,2 while the results of students’ mathematics learning data an average score is 19,6. Based on data analysis known that: (1) comics media mathematics are positive and significant impact on motivation to mathematic learn, where t test was obtained thitung = 3,1914 ˃ ttabel = 1,692. The index determination I = 12,5%, it means that comics media mathematics accounted 12,5% with motivation onof mathematic learning; (2) comics media mathematics are positive and significant with the results of students’ mathematics learning. Based on t test was obtained thitung = 6,19 ˃ ttabel = 1,692. The index determination I = 53,77%, it means that comics media mathematics accounted for 53,77% of the increase in the results of students’ mathematics learning.